INOVASI MEDIA PEMBELAJARAN INTERAKTIF BANGUN RUANG MATEMATIKA BERBASIS AUGMENTED REALITY DAN ANDROID - Yasifiati Hia; Zulfahmi Indra; Denny Haris (Smart Education, 2026)
Abstract: Learning three-dimensional (3D) geometric solids remains one of the persistent challenges in mathematics education because students must imagine abstract spatial objects that textbooks can only present in two dimensions. This condition often lowers students' learning interest and hinders their spatial reasoning, particularly at the junior high school level. This study aims to design and develop an interactive learning medium in the form of an Augmented Reality (AR)-based pocket book for teaching geometric solids (cube, cuboid, triangular prism, and quadrilateral pyramid) using the Marker Based Tracking method on the Android platform. The research employed a Research and Development (R&D) approach following the ADDIE model, covering the stages of analysis, design, development, implementation, and evaluation. The application was built using Unity3D as the development engine and Vuforia SDK as the marker recognition library, then tested on mobile devices to measure accuracy, latency, frame rate, device compatibility, and marker-detection distance. The results show that the application can detect markers at a distance of 8-77 cm with a latency of 1000-2000 ms and a frame rate of 15-30 fps, and it runs properly on Android devices from version 7.0 onward. These findings indicate that the pocket book is feasible as an alternative interactive medium to strengthen students' spatial imagination of geometric solids. Keywords: augmented reality; media pembelajaran; bangun ruang; marker based tracking; android. Abstrak: Pembelajaran bangun ruang sisi datar masih menjadi salah satu materi matematika yang sulit dipahami siswa karena menuntut kemampuan membayangkan objek tiga dimensi yang di dalam buku teks hanya digambarkan secara dua dimensi. Kondisi ini kerap menurunkan minat belajar sekaligus menghambat kemampuan spasial siswa, terutama di jenjang sekolah menengah pertama. Penelitian ini bertujuan merancang dan mengembangkan media pembelajaran interaktif berupa buku saku berbasis Augmented Reality (AR) untuk materi bangun ruang sisi datar (kubus, balok, prisma segitiga, dan limas segi empat) dengan metode Marker Based Tracking berbasis Android. Penelitian menggunakan pendekatan Research and Development (R&D) dengan model ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Aplikasi dibangun menggunakan Unity3D sebagai mesin pengembang dan Vuforia SDK sebagai pustaka pengenal marker, kemudian diuji pada perangkat bergerak untuk mengukur akurasi, latensi, frame rate, kompatibilitas perangkat, dan jarak deteksi marker. Hasil pengujian menunjukkan bahwa aplikasi mampu mendeteksi marker pada jarak 8-77 cm dengan latensi 1000-2000 ms dan frame rate 15-30 fps, serta dapat berjalan baik pada perangkat Android versi 7.0 ke atas. Temuan ini mengindikasikan bahwa buku saku tersebut layak digunakan sebagai media interaktif alternatif untuk memperkuat imajinasi spasial siswa terhadap bangun ruang. Kata kunci: augmented reality; media pembelajaran; bangun ruang; marker based tracking; android.